An improved medium for the anaerobic growth of Paracoccus denitrificans Pd1222 - Hahnke, Stefanie M.; Moosmann, Philipp; Erb, Tobias J.; Strous, Marc (Frontiers in Microbiology, 2014)
Paracoccus denitrificans is a well studied model organism with respect to its aerobic and anaerobic respiratory enzymes. However, until now, the growth medium for this organism has not been optimized for anaerobic growth. In particular, the requirements of P. denitrificans for trace elements are not well known. In the present study we aimed to improve growth rates of P. denitrificans Pd1222 on a defined medium under anoxic conditions. We designed media containing different combinations of trace elements at various concentrations, and tested their performance against previously reported media. Our results suggest that growth rate and yield depend on the availability and concentration of trace elements in the medium. A chelated trace element solution was more suitable than an acidified trace element solution. Highest growth rates were achieved with medium comprising the trace elements iron, manganese, molybdenum, copper and zinc ranging from 0.1 to 9 µM. On this medium, P. denitrificans Pd1222 grew with a generation time of 4.4 hours under anoxic conditions and 2.8 hours under oxic conditions. Diauxic growth was clearly shown with respect to nitrate and nitrite reduction under anoxic conditions.